1994
DOI: 10.1128/jvi.68.1.510-516.1994
|View full text |Cite
|
Sign up to set email alerts
|

Passage through mitosis is required for oncoretroviruses but not for the human immunodeficiency virus

Abstract: The human immunodeficiency virus productively infects and integrates into cells that have been arrested in the cell cycle with either gamma irradiation or aphidicolin. Integration by oncoretroviruses such as the murine leukemia virus (MuLV), on the other hand, depends on cell proliferation. Although the entire cell cycle is not necessary for MuLV infection, it is essential that the infected cells pass through mitosis. The long terminal repeat circle junction, a marker for nuclear entry, is first observed in Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
216
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 717 publications
(226 citation statements)
references
References 29 publications
5
216
0
5
Order By: Relevance
“…It was further Zho et al, 1993;Connor and Ho, 1994;van't Wout et al, shown that viruses carrying a double lysine to threonine 1994; Cornelissen et al, 1995;O'Brien and Pomerantz, substitution in this region ( 26 KK→TT) displayed levels of 1996). The ability of HIV-1 to infect non-dividing cells infectivity and replication that were diminished in nonproductively contrasts with the finding that replication of dividing target cells but indistinguishable from correspondthe oncogenic retrovirus murine leukemia virus (MLV) is ing wild-type viruses in dividing cells (Bukrinsky et al, restricted to dividing (proliferating) cells (Roe et al, 1993;Lewis and Emerman, 1994). This key difference between 1993a; Heinzinger et al, 1994;von Schwedler et al, these studies has been the direct assignment of NLS function according to conventional criteria.…”
Section: Introductionmentioning
confidence: 99%
“…It was further Zho et al, 1993;Connor and Ho, 1994;van't Wout et al, shown that viruses carrying a double lysine to threonine 1994; Cornelissen et al, 1995;O'Brien and Pomerantz, substitution in this region ( 26 KK→TT) displayed levels of 1996). The ability of HIV-1 to infect non-dividing cells infectivity and replication that were diminished in nonproductively contrasts with the finding that replication of dividing target cells but indistinguishable from correspondthe oncogenic retrovirus murine leukemia virus (MLV) is ing wild-type viruses in dividing cells (Bukrinsky et al, restricted to dividing (proliferating) cells (Roe et al, 1993;Lewis and Emerman, 1994). This key difference between 1993a; Heinzinger et al, 1994;von Schwedler et al, these studies has been the direct assignment of NLS function according to conventional criteria.…”
Section: Introductionmentioning
confidence: 99%
“…While standard retrovirus-based vectors integrate the transgene into the genome of the target cells and offer sustained expression of the transgene, they infect only dividing cells. 5 Therefore, this limits their use in non-dividing cells such as cultured primary cells that permanently exit the cell division cycle but remain viable for extended periods of time. 6 The development of human immunodeficiency virus (HIV, lentivirus) based vector systems has provided a delivery system that offers infection of both dividing and non-dividing cells and integration of the transgenes into the genome.…”
Section: Introductionmentioning
confidence: 99%
“…e viral core containing a single cDNA copy from the double stranded genomic RNA is transported to the nucleus and it is integrated into the host cell chromosomes following the activity of integrase (IN). While simple -retroviruses require the disappearance of the nuclear membrane during cell division, complex retroviruses (lentiviruses) can actively transport the core to the cell nucleus without requiring mitosis [26,27]. us, retrovirus vectors only transduce cells during mitosis, while lentiviral vectors can transduce cells independently on their division status.…”
Section: The Retroviral Life Cycle and Retroviral Vectorsmentioning
confidence: 99%
“…While the advantages of simple retrovirus vectors are the lack of genome-encoded viral proteins and persistent gene expression aer vector integration, they also present important limitations. e main ones are virion instability [35], relatively low titers [36], the inability to transduce quiescent cells [27,37], and �nally, insertional mutagenesis [38][39][40]. Interestingly, these shortcomings can be largely overcome by using lentivectors, mainly developed from human immunode�ciency virus (HIV)-1 [41][42][43].…”
Section: The Retroviral Life Cycle and Retroviral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation